Nepal’s transitional development and son preference - Sana, Mayuko (Nepal Sociological Journal, 2025)
This study aimed to consider the conditions under which son preference weakens, starting with Balla and Kaur (2015), who showed that son preference weakens as one moves up the social ladder. Data collected from the questionnaire survey were analyzed using SPSS. The findings indicate that members of the upper class have a weak son preference, not only because of economic stability but also because they benefit from meritocracy. Based on these results, this study suggests three structural factors that give rise to son preference: a situation in which individuals’ economic and social security depends on their families, the superiority of sons in inheriting the family lineage, and not receiving the benefits of meritocracy.